Patient agenda setting in respiratory outpatients: A randomized controlled trial. (November 2015) - Early, Frances; Everden, Angharad JT; O'Brien, Cathy M; Fagan, Petrea L; Fuld, Jonathan P
Soliciting a patient's agenda (the reason for their visit, concerns and expectations) is fundamental to health care but if not done effectively outcomes can be adversely affected. Forms to help patients consider important issues prior to a consultation have been tested with mixed results. We hypothesized that using an agenda form would impact the extent to which patients felt their doctor discussed the issues that were important to them. Patients were randomized to receive an agenda form to complete whilst waiting or usual care. The primary outcome measure was the proportion of patients agreeing with the statement 'My doctor discussed the issues that were important to me' rated on a four-point scale. Secondary outcomes included other experience and satisfaction measures, consultation duration and patient confidence. There was no significant effect of agenda form use on primary or secondary outcomes. Post hoc exploratory analyses suggested possible differential effects for new compared to follow-up patients. There was no overall benefit from the form and a risk of detrimental impact on patient experience for some patients. There is a need for greater understanding of what works for whom in supporting patients to get the most from their consultation.